ield performance and stability analysis of okra (Abelmoschus esculentus L. MOENCH) accessions using AMMI and GGE biplots.: G x E Analysis of Okra Accessions - Komolafe, Ronke (Journal of Agricultural Sciences (Belgrade), 2022)
Identification of adaptable, stable and high yielding genotypes under varying environmental conditions prior to release pose a lot of challenge to plant breeders in selecting the best genotypes of okra. The genotype × environment interaction is of major challenge to plant breeders because a large interaction can reduce selection gain and make the identification of superior cultivars difficult. The objectives of this study were to evaluate the performance of okra accessions in different environments and identify high yielding and stable accession so as to select parent for further breeding work. Seventeen accessions of okra were evaluation at Akure during the rainy season of 2018, at Akure and Oye during the rainy season of 2019; and Akure during the rainy season of 2020, making a total of four environments. Additive main effect and multiplicative interaction and GGE-biplots were employed for the evaluation of G × E interaction and stability studies in the four environments. The AMMI analysis identified NGB00378a as the most stable accession and high yielder. Also, GGE biplot identified NGB00378a as highly stable and high yielder while NGB00355 was highest yielder but fairly stable. But NGB00378a combines good performance with stability. Therefore, NGB00378a is an ideal accession and recommended.